PENGEMBALIAN ASET NEGARA TERHADAP TINDAK PIDANA KORUPSI MELALUI KERJASAMA INTERNASIONAL BERDASARKAN UNDANG – UNDANG NOMOR 7 TAHUN 2006 TENTANG PENGESAHAN UNITED NATlONS CONVENTION AGAINST CORRUPTION (UNCAC) - ANDI SAPUTRA; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The act of corruption is a violation of the social rights and economic rights of the people, so that the criminal act of corruption can not be classified as ordinary crimes but has become extra-ordinary crimes, so in an effort to enforce it can no longer be done "normally" but extraordinarily extra-ordinary enforcement.The eradication of corruption is a series of actions to prevent and combat corruption through coordination, supervision, monitoring, investigation, investigation, prosecution and trial in court, with community participation based on prevailing laws and regulations, In conducting the process of returning assets resulting from the criminal act of corruption,but in implementation there are constraints caused by: different legal system, banking and financial system the strictness of the country in which the asset is located, the practice of running the law, and the resistance of the party to which the asset is to be taken by the government.Recovery of state financial losses with state financial recovery efforts in corruption acts in reality still faces obstacles both at the procedural level and on the technical level. At the procedural level requires certain legal instruments appropriate in accordance with the modus operandi of the crime and the object of the legal matter, Return of assets resulting from criminal acts of corruption is still limited to the return of assets in the country and there is no provision governing the return of assets assets of corruption abroad that are placed abroad, then the necessary legislation on the return of assets resulting from criminal acts of corruption as a legal foundation as well as the authority to implement international cooperation in the recovery of assets resulting from criminal acts of corruption.